2016
DOI: 10.5513/jcea01/17.4.1798
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of European cultivars of common wheat (Triticum aestivum L.) based on RAPD and protein markers

Abstract: The knowledge of genetic diversity of wheat genotypes based on DNA and protein polymorphism is very important for breeding programs (MAS). The objective of this study was to assess the genetic variability among twentyfour European cultivars of common wheat using SDS-PAGE and RAPD techniques. Protein electrophoreses showed 31 polymorphic bands with 63.2% polymorphism. Genetic similarity based on Jaccard´s coefficient ranged from 0.067 to 0.933. Also twelve different Glu-1 encoded allelic variants were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is well known that genetic diversity is the basis of biological diversity, and thus, it plays a key role in making progress in crop breeding in future (Jisha et al, 2015;Pournosrat et al, 2018). Evaluation of genetic diversity using molecular markers is a cornerstone for understanding genome structure, the characterization and maintenance of genetic variation on plant germplasm, identifying genes underlying important traits and devising optimal breeding strategies for crop improvement (Kuťka-Hlozákovás et al, 2016). Further scope of crop improvement depends on the conserved use of genetic variability and diversity in plant breeding programmes and use of new biotechnological tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that genetic diversity is the basis of biological diversity, and thus, it plays a key role in making progress in crop breeding in future (Jisha et al, 2015;Pournosrat et al, 2018). Evaluation of genetic diversity using molecular markers is a cornerstone for understanding genome structure, the characterization and maintenance of genetic variation on plant germplasm, identifying genes underlying important traits and devising optimal breeding strategies for crop improvement (Kuťka-Hlozákovás et al, 2016). Further scope of crop improvement depends on the conserved use of genetic variability and diversity in plant breeding programmes and use of new biotechnological tools.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, relatively cheap techniques that demand less sophisticated laboratory equipment could be the appropriate choice (Aman, 1995;Baloch et al, 2014) to make reasonable scientific advancements. However, protein markers are useful tools to identify cultivar and classification of crop species to study genetic diversity, thereby improving the efficiency of plant breeding programs (Gianibelli et al, 2001;Kuťka-Hlozákovás et al, 2016;Pe´rez de, 1993;Sharma and Krishna, 2017). Among biochemical techniques, Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) due to its simplicity, minimum cost in time and labor, and effectiveness is commonly used in the studies of plants genetic diversity (Abou-Ellail et al, 2014;Ahmed et al, 2010;Masoumi et al, 2012;Radwan et al, 2013;Sadia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This present study demonstrated the protein variation among the M. officinalis populations can be seriously taken into account in molecular studies. Furthermore, the electrophoresis of leaf proteins can be utilized as an effective strategy in the programs involved with M. officinalis conservation [15]. The observed differences among the accessions would be of immediate importance for development of the M. officinalis gene bank and may be used in hybridization and breeding programs to identify diverse parental combinations and creating segregating progeny with high genetic diversity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Morphological traits have a number of limitations, including low polymorphism, low heritability, late expression, and may be controlled by epistasis and pleiotropic gene effects Nakamura [11], while molecular markers such as protein markers reflect the genotype more directly, independent of environmental influences [12,13]. Protein markers are useful tools to identify cultivar, registration of new varieties and classification of crop species to study genetic diversity, thereby improving the efficiency of plant breeding programs [14][15][16]. Among biochemical techniques, Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) due to its simplicity, minimum cost in time and labor, and effectiveness is commonly used in the studies of plants genetic diversity [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, morphological and agronomical traits have several limitations such as low polymorphism and heritability and may be controlled by epistasis and pleiotropic gene effects (Danaeipour et al, 2019 ), while biochemical and molecular markers reflect the genotype more directly, independent of environmental impact (Ernst et al, 2017 ). Biochemical markers and specifically seed protein markers are valuable tools to identify cultivar, register new varieties, and characterize plant species to study genetic diversity (Kutka Hlozakova et al, 2016 ; Sharma and Krishna, 2017 ). Most of the proteins are unique and suitable to be used as markers in genetic diversity analyses at interand intra-population levels (Asante et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%